Effectiveness of acupuncture on myofascial release in the treatment of low back pain (Research, Society and Development, 2023)
Low back pain has become a worldwide public health problem. In most cases, it can be classified as chronic when the symptom persists for more than twelve weeks and has a nonspecific origin. The objective of this bibliographic review was to analyze the benefit of acupuncture in myofascial release in the treatment of low back pain in patients through the analysis of scientific articles. The review work was the product of analysis and bibliographic research carried out in the Google Scholar, Oxford Academic, Science Direct, Taylor & Francis and Web of Science databases, carried out from October to December 2022. The selection of articles was carried out with based on two steps: adaptation of the title and then reading it in full. The number of people with low back pain is considered an increasing problem, reaching from 50% to 80% of consultations in the health area. Acupuncture can be an alternative treatment for patients suffering from low back pain, as research has shown promising results in conjunction with myofascial release that has the benefit of reducing chronic low back pain, in order to provide a better quality of life for their patients. carriers.